Case report: Olanzapine-associated water retention, high blood pressure, and subsequent preterm preeclampsia - Izsak, Julia; Falari, Dimitra; Arnbert, Pia; Pouragheli, Daniel; Kindblom, Jenny M.; Lasaitiene, Daina (Frontiers in Psychiatry, 2023)
Olanzapine is one of the most frequently used antipsychotic medications during pregnancy, but information about its safety and adverse effects profile during pregnancy is scarce. We herein describe a case of a pregnant woman with several psychiatric disorders who developed water retention, hypertension, and subsequent preterm preeclampsia 3 weeks after initiation of treatment with olanzapine. To the best of our knowledge, this is the first case of olanzapine-associated preeclampsia described in literature.